DIFFICULTIES EXPERIENCED BY FAMILY CAREGIVERS IN THE DAILY CARE OF THE ELDERLY - Kelvin Botelho Dias, Icaro; Cordeiro Muniz Silva, Elisabete; Soares da Silva Menezes, Agna; Ferreira da Silva Junior, Rene; Isabel Veloso Fonseca Antunes, Veronica; Dias Prado, Ticiane; Ferreira Jesus, Valdinei; Gonçalves Fagundes, Giovanna; Souza Miranda, Bruno; Antunes Aquino Cardoso Gonçalves, Sueli; Edson de Oliveira, Diego; Jardim Neiva, Ricardo; et al. (Health and Society, 2024)
Introduction: care for the elderly requires family caregivers to reorganize family roles, in addition to constant and holistic support, when there are failures in this process, significant negative outcomes may occur for the caregiver. Objective: to know the difficulties experienced by family caregivers in the daily care of the elderly. Methodology: descriptive study of qualitative approach conducted with family caregivers registered in a Basic Health Unit. A questionnaire was used for sociodemographic characterization and a semi-structured interview with a guide question. Content analysis was used for data analysis. Results: the conditions to which caregivers are exposed entail important challenges that require family support and health services. The study revealed constant episodes of conflicts, resulting in the absence of division of responsibilities by family members. Conclusion: the difficulties experienced by the caregiver were questions related to sleep quality, overload, family relationships and feelings of ambivalence.